A Comparative Analysis of the Piece “Op. 6 No: 2 Nocturne” by Clara Wieck Schumann, one of the Female Composers of the Romantic Period, with the Nocturnes of Frederic François Chopin - M. Nevra Küpana; İlayda Çetin (Akademik İncelemeler Dergisi)
This study includes a comparative analysis of the composition titled "Op.6 No.2 Nocturne" by Clara Wieck Schumann, a female composer from the Romantic era, with the nocturnes of Frederic François Chopin. The purpose of this research is to determine the similarities and differences between Clara Wieck Schumann's aforementioned work and the works of Frederic François Chopin, who is an important male composer of the same period, in the same form. In this study, firstly a literature review was conducted. Then, in line with the purpose of the research, a comparison of Clara Wieck Schumann's composition titled "Op.6 No:2 Nocturne" with Frederic François Chopin's compositions titled "Op.27 No:2 Nocturne" and "Op.9 No:2 Nocturne" was carried out using harmonic, form and style analysis methods. When examining the harmonic analysis of the compositions, including accompaniment and chord styles, ornaments, rhythmic structures, and stylistic features, it is observed that they exhibit a similar emotion and style. Accordingly, it can be inferred that Clara Wieck Schumann was influenced by Frederic François Chopin in her composition. The conducted analysis is of importance not only in determining the similarities and the differences between the works of both composers, but also in terms of increasing the visibility of female composers in the music world.